2016
DOI: 10.1038/eye.2015.261
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy light bulbs, computers, tablets and the blue light hazard

Abstract: The introduction of low energy lighting and the widespread use of computer and mobile technologies have changed the exposure of human eyes to light. Occasional claims that the light sources with emissions containing blue light may cause eye damage raise concerns in the media. The aim of the study was to determine if it was appropriate to issue advice on the public health concerns. A number of sources were assessed and the exposure conditions were compared with international exposure limits, and the exposure li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 6 publications
4
122
0
5
Order By: Relevance
“…The rationale for blue light‐inducing retinal injury derives primarily from animal model and cell culture studies, where retinal changes have been reported following exposure to high intensity blue light. More recently, O'Hagan et al . investigated blue light exposure from electronic devices, such as computer screens and mobile phones, and noted that the amount of blue light emitted from these devices was almost 1000‐fold less than the levels in natural daylight.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for blue light‐inducing retinal injury derives primarily from animal model and cell culture studies, where retinal changes have been reported following exposure to high intensity blue light. More recently, O'Hagan et al . investigated blue light exposure from electronic devices, such as computer screens and mobile phones, and noted that the amount of blue light emitted from these devices was almost 1000‐fold less than the levels in natural daylight.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the weighted values were summed to give the irradiance for comparison with the guideline exposure limit. It was found that under even extreme long‐term viewing conditions, none of the assessed sources exceeded the guideline limits and therefore extensive exposure to digital device‐emitted radiation should not raise concerns for public eye health . However, these devices are known to emit strongly in the short‐wavelength part of the visible spectrum and blue light is currently considered to have the strongest effect in synchronizing human circadian rhythm .…”
Section: Digital Age and Eye Healthmentioning
confidence: 99%
“…[17] With the increasing popularity of blue-rich LED-backlight display devices, such as mobile smartphones, ultraportable tablets, and computer screens, our eyes are exposed to more blue light than in the past. There has been a surge of new ophthalmic aids including intraocular lenses[18] and spectacle lenses designed with a rationale to protect the eyes from potential photochemical damages.…”
Section: Introductionmentioning
confidence: 99%